Materials of the International Conference of Modern Information Services for Improvement Study Quality Project (MISISQ): Involvement. Creativity. Sustainability, held on 27-28, September 2018 in Chisinau, Republic of Moldova (Confluenţe Bibliologice, 2018)
This volume incorporates the materials of the MISISQ International Conference: Involvement. Creativity. Sustainability, held on September 27-28, 2018 in Chisinau, Republic of Moldova, 2 years after the official end of the Project.
Keywords: MISISQ project